Measurement of oxidative metabolism of the working human muscles by near infrared spectroscopy - (:unkn) unknown (My University, 2006)
Monitoring the oxygenation of skeletal muscle tissues during rest to work transient provides valuable information about the performance of a particular tissue in adapting to aerobic glycolysis. In this paper we analyze the temporal relation of O2 consumption with deoxy-hemoglobin (Hb) signals measured by functional Near Infrared Spectroscopy (fNIRS) technique during moderate isotonic forearm finger joint flexion exercise under ischemic conditions and model it with a mono exponential equation with delay. The time constants of fitting equation are questioned under two different work loads and among subjects differing in gender. Ten (6 men and 4 women) subjects performed isotonic forearm finger joint flexion exercise with two different loads. It is shown that under the same load, men and women subjects generate similar time constants and time delays. However, apparent change in time constants and time delays were observed when exercise was performed under different loads. When t-test is applied to compare the outputs for time constants between 0.41202 Watts and 0.90252 Watts, P value of 9.3445×10-4 < 0.05 is observed which implies that the differences between the time constants are statistically significant. When the same procedure is applied for the time delay comparison, P value of 0.027<.05 is observed which implies that also the differences between the time delays are statistically significant.
Keywords: Functional near-infrared spectroscopy (fNIRS); Gender difference; Muscle; Oxidative metabolism